2022
DOI: 10.3390/foods11223646
|View full text |Cite
|
Sign up to set email alerts
|

Designing Immersive Sustainable Food Experiences in Augmented Reality: A Consumer Participatory Co-Creation Approach

Abstract: In light of the current debate on the impact of our current food system on climate change and related mitigation strategies, addressing the acceptance of sustainability aspects within consumer behavioral issues is of vital importance. However, the field remains mute on how those strategies can be designed and employed effectively to stimulate sustainable food consumption behavior. Immersive narrative design is a promising approach to engaging consumers in this context. Within this study, we shed light on how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…The findings of this study show that customer sensory experience services have a significantly negative effect on customer co-creation behavior. Surprisingly, previous studies have recognized experience as a crucial building block for positively fostering customer behavioral responses, such as co-creation behavior or engagement behavior with a company or product producer (Spena et al, 2012;Han et al, 2022). However, the results of the current study were not consistent with this prior research that indicated customer experience directly influenced building customer co-creation to provide feedback or their experience to the company or producer.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of this study show that customer sensory experience services have a significantly negative effect on customer co-creation behavior. Surprisingly, previous studies have recognized experience as a crucial building block for positively fostering customer behavioral responses, such as co-creation behavior or engagement behavior with a company or product producer (Spena et al, 2012;Han et al, 2022). However, the results of the current study were not consistent with this prior research that indicated customer experience directly influenced building customer co-creation to provide feedback or their experience to the company or producer.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, the meat was not yet on the market, which makes its story a bit unrelatable. However, the meat may be good for the future (Han et al, 2022). In addition, we considered the customer experience to be a customer perception of meat that was unclear regarding taste and smell between the market chicken meat and the healthy chicken meat (i.e., the KKU1 Premium Chicken).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on AR and consumer interaction have mostly been carried out in the following areas: the attractiveness of AR applications for consumers (Grzegorczyk et al, 2019;Scholz & Smith, 2016), the effect of AR applications on consumer behavior (De Amorim et al, 2022;Hassan et al, 2018;Lavoye et al, 2021;Mocanu, 2016;Smink et al, 2022), segmenting consumer attitudes towards AR (Romano et al, 2022), consumer AR systems (Azuma, 2019;Stoyanova et al, 2013), AR ads and consumer engagement (Han et al, 2022;Martin, 2019;Saleem et al, 2022), mobile AR adoption in a consumer context (Aw et al, 2023;Chen et al, 2022;Paulo et al, 2018), use of AR in consumer marketing (Wedel et al, 2020), use of AR during the COVID-19 pandemic period (Medina-Robalino et al, 2022;Riar et al, 2022), and use of AR in online retailing (Fan et al, 2020;Schmidt et al, 2022).…”
Section: Literature Review Phygital Marketing and Ar Applicationsmentioning
confidence: 99%
“…Overall, historical narratives have a direct influence on purchase trends. Consumer reviews, immersive experiences, and government asset purchases are examples of how historical narratives can shape consumer perceptions, emotions, and decision-making processes (Laer et al, 2018;Han et al, 2022;Fieldhouse et al, 2017). Understanding the impact of historical narratives on consumer behavior is crucial for marketers and policymakers to effectively engage consumers and drive purchase trends.…”
Section: Online Grocery Shopping Trends In Pakistanmentioning
confidence: 99%